SISTEM SOSIAL, KULTURAL, DAN KEPRIBADIAN DALAM NOVEL EDENSOR KARYA ANDREA HIRATA (SOCIAL, CULTURAL, AND PERSONALITY SYSTEM IN THE EDENSOR NOVEL BY ANDREA HIRATA) - Gesit Aprianto (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
Social, Cultural, and Personality System in the “Edensor” Novel by Andrea Hirata. This study discusses the social, cultural, and personality systems found in the “Edensor” novel. This research is a qualitative research with a literary anthropological approach. The object of this research is a novel entitled "Edensor" by Andrea Hirata and focuses on social systems, cultural systems, and personality systems. The data used in this study are all texts in the novel "Edensor" which contain social, cultural, and personality systems. The data obtained were analyzed using the theory developed by Tallcot Parson. Based on the analysis, it can be seen that in Andrea Hirata's Edensor novel there are social systems, cultural systems, and personality systems. The social systems found include community subsystems, fiduciary systems, government systems, and economic systems. The cultural systems found include the norms subsystem, activity subsystem, and work subsystem. The personality system found includes motivation and needs.Key words: social system, cultural system, personality system, literary anthropology, Talcott Parsons' theorySistem Sosial, Kultural, dan Kepribadian dalam Novel “Edensor” karya Andrea Hirata. Penelitian ini membahas sistem sosial, budaya, dan kepribadian yang terdapat pada novel “Edensor”. Penelitian ini berupa penelitian kualitatif dengan pendekatan antropologi sastra. Objek dari penelitian ini adalah novel berjudul “Edensor” karya Andrea Hirata dan berfokus pada sistem sosial, sistem kultural, dan sistem kepribadian. Data yang digunakan dalam penelitian ini adalah semua teks dalam novel “Edensor” yang mengandung sistem sosial, budaya, dan kepribadian. Data-data yang diperoleh dianilisis menggunakan teori yang dikembangkan oleh Tallcot Parson. Berdasarkan analisis yang dilakukan, dapat diketahui bahwa di dalam novel Edensor karya Andrea Hirata terdapat sistem sosial, sistem kultural, dan sistem kepribadian. Sistem sosial yang ditemukan meliputi subsistem komunitas kemasyarakatan, sistem fiduciary, sistem pemerintahan, dan sistem ekonomi. Sistem kultural yang ditemukan meliputi subsistem norma, subsistem aktivitas, dan subsistem karya. Sistem kepribadian yang ditemukan meliputi motivasi dan kebutuhan.Kata-kata Kunci: sistem sosial, sistem kultural, sistem kepribadian, antropologi sastra, teori Talcott Parsons